2003
DOI: 10.1054/jhsb.2002.0866
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Function After Excision of the Pisiform

Abstract: The pisiform bone may provide mechanical stability to the ulnar column of the wrist by preventing triquetral subluxation. Thus, surgical excision of the pisiform might cause loss of function to the wrist. We performed a functional evaluation of 20 hands in 20 patients who had undergone pisiformectomy for pisotriquetral joint dysfunction. At a mean follow-up of 65 months, 15 patients had complete relief of symptoms and five continued with mild discomfort. Compared with the unaffected wrist, there were no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 9 publications
1
39
0
1
Order By: Relevance
“…Lam et al investigated the clinical and functional outcome of the wrist after pisiformectomy for pisotriquetral joint dysfunction and concluded that there were no significant differences in grip strength and range of wrist motion [12]. They reported no postoperative FCU dysfunction and subluxation of the FCU tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al investigated the clinical and functional outcome of the wrist after pisiformectomy for pisotriquetral joint dysfunction and concluded that there were no significant differences in grip strength and range of wrist motion [12]. They reported no postoperative FCU dysfunction and subluxation of the FCU tendon.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Although a good outcome has been described after pisiformectomy, there is not always complete relief of symptoms. 14 Lam et al 14 performed a functional evaluation of 20 hands in 20 patients who had undergone pisiformectomy for PTJ dysfunction. At a mean follow-up of 65 months, 15 patients had complete relief of symptoms and 5 continued with mild discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…This hypermobility can result in repeated impingement, causing neuritis of the ulnar nerve in Guyon's canal and potentially spasm of the ulnar artery ( Figure 2) [4]. Excision of the pisiform bone is reliable in those cases that involve dysfunction of the pisotriquetral joint, and concerns about its damage to the stability of the wrist have been laid to rest by Lam et al in 2003 in their series of 20 patients [5].…”
Section: Discussionmentioning
confidence: 99%